The effects of biocides on the growth of aerophytic green algae (Chlorella sp.) isolated from a cave environment - Nikolić, Nataša; Subakov Simić, Gordana; Golić, Igor; Popović, Slađana (Archives of Biological Sciences, 2021)
Paper description: Lampenflora communities have a negative impact on caves and can cause biodeterioration. Hydrogen peroxide has been used for lampenflora removal but other biocides have not been utilized in cave environments. This study explored the effects of hydrogen-peroxide, a commercial solution containing salicylic acid and a product containing chlorine dioxide, on green algae growth under laboratory conditions, by determining chlorophyll a concentration before and after treatment. All three biocides prevented green algae growth, with chlorine dioxide being the most effective. Further study is necessary to assess the effects of biocides on limestone and cave environments. Abstract: Lampenflora communities of bacteria, cyanobacteria, algae, mosses and lichens colonize illuminated show-caves as a consequence of disturbances to the caves’ ecological equilibrium. These communities have unesthetic impacts and can cause the biodeterioration of limestone. A 15% hydrogen peroxide solution was proposed for use as an ecological agent for the safe removal of these microorganisms. This study tested the effects of three different biocides (hydrogen peroxide, a commercial solution containing salicylic acid and a product containing chlorine dioxide as the active component), on the growth of green algae (Chlorella sp.), which are frequently encountered in lampenflora communities. Chlorella sp. was treated with the biocides under laboratory condition, and chlorophyll a (Chl a) concentrations were measured 1 h, 3 days, 7 days and 10 days after treatment. The change in Chl a concentration was compared to the untreated control group at each time point. All three biocides prevented the growth of green algae and the product containing chlorine dioxide appeared to be the most effective growth inhibitor. Hydrogen peroxide is known to suppress lampenflora growth in caves, and further studies on other biocides remain necessary to identify a solution that is both ecologically safe and economically feasible.